2020
DOI: 10.1371/journal.pone.0229471
|View full text |Cite
|
Sign up to set email alerts
|

Online shopping green product quality supervision strategy with consumer feedback and collusion behavior

Abstract: With the development of e-commerce, online shopping has become one of the most important consumer channels. However, the lack of government supervision, insufficient review of e-commerce platforms, illegal sales of online sellers and invalid consumer complaints have led to frequent green product quality problems during online shopping. Therefore, this paper considers that the online seller may be driven by interests, colluding with the e-commerce platform and selling low quality green product. At the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…This was different from the reality that the platform was directly responsible for managing the settled enterprises [33]. Secondly, although the government supervision was introduced into research studies, these studies assumed that when the government implemented supervision, it could discover the enterprises' illegal behavior, which was not consistent with reality [49,50]. In reality, even if the government earnestly fulfilled its regulatory duties, some illegal enterprises and platforms would inevitably be missed due to the limitation of government's regulatory resource.…”
Section: The Application Of Evolutionary Game Theorymentioning
confidence: 92%
See 2 more Smart Citations
“…This was different from the reality that the platform was directly responsible for managing the settled enterprises [33]. Secondly, although the government supervision was introduced into research studies, these studies assumed that when the government implemented supervision, it could discover the enterprises' illegal behavior, which was not consistent with reality [49,50]. In reality, even if the government earnestly fulfilled its regulatory duties, some illegal enterprises and platforms would inevitably be missed due to the limitation of government's regulatory resource.…”
Section: The Application Of Evolutionary Game Theorymentioning
confidence: 92%
“…For example, He and Zhu (2020) focused on the collusion behavior between online companies and platforms. Researchers found that enhancing the loss-sharing relationship between the online seller and the e-commerce platform can prevent collusion behavior [49]. built a supervision game model between the governmental quality supervision department and the online shopping platform.…”
Section: The Application Of Evolutionary Game Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [2] designed a quality game model between the online shopping platform and the government and explained the essential role of government supervision in online shopping quality assurance. He and Zhu [11] focused on the green product quality in online shopping and explored the impact of consumer feedback on the three-party quality evolutionary game of "online shopping platform-online seller-government 2 Complexity regulatory authority," and found that the government should encourage consumers to complain, improve the green product certification mechanism, and severely punish violations in the transaction process to control the green product quality of online shopping. He et al [12] analysed the impacts of quality dropping rate and products' deterioration rate on the company's delivery time decisions, pricing and inventory decisions in a dual-channel supply chain that combined online direct sale channel and traditional offline channel.…”
Section: Online Shopping Quality Game Under the Government Supervisionmentioning
confidence: 99%
“…So, their purchasing behaviour shifts to eco-friendly goods, this leads to a change in the production process of the industry, compelling to adopt "Go Green Strategy" in all aspect of the business. He & Zhu (2020) investigated that minimizing the probability of low-quality green products offered by the e-marketer, encourage consumers gathering in quality observation work together, and nurture their consciousness of safeguarding. Mayank & Amit (2013) observed in their research that the consumers and manufacturers are deeply serious about the environment concerns and green products and practices.…”
Section: Introductionmentioning
confidence: 99%